Evaluation of Teaching Performance of Mathematics Teachers in Thamar Schools in Yemen during the War in light of the effective Teacher Evaluation Model for (Marzano) - Alhadoor, Zaid Ahmad Nasser (Journal of Educational and Psychological Sciences, 2021)
The present research aimed at evaluating the teaching performance of Mathematics teachers in Thamar city schools in Yemen during the war in light of the effective teacher evaluation model for (Marzano). To achieve this aim, the descriptive approach was employed, and a note-card was developed based on the criteria and indicators of the special strategies and behavior originating from the effective evaluation model for teacher developed by (Marzano). This card consisted of (41) indicators distributed on three sections, and it was applied to a cluster-random sampling on (64) Mathematics teachers in Thamar primary and secondary schools. The study results revealed that the overall performance of participants was on average. Similarly, the results revealed that the level of performance of the participants in both routine skills and immediate skills was on average. However, the results showed that there was a low level of performance in skills pertinent to the content. The study results showed statistically significant differences in the level of teaching performance of Mathematics teachers for the variable (type the school) and in favor of private school teachers. The study results also showed that there were statistically significant differences in the level of teaching performance of Mathematics teachers for the variable (gender), in favor of the female teachers. In addition, the study results showed that there were statistically significant differences in the level of teaching performance of Mathematics teachers for the variable (years of experience) and in favor of teachers whose experience is less than (5) years, and those whose experiences ranged between (5-10) years, compared to teachers whose experiences were more than (10) years of experience, Conducting professional development courses for mathematics teachers in accordance with the criteria of effective teacher evaluation, neutralizing educational institutions from war and disbursing teachers’ salaries.